Investigating the moderating effect of family on the relationship between entrepreneurial orientation and success of enterprise: case of Pakistani manufacturing SMEs. (2015) - Akhtar, Chaudhry Shoaib; Ismail, Kamariah; Hussain, Jawad; Umair-ur-Rehman, Muhammad
Entrepreneurial orientation (EO) is one of the widely researched areas in entrepreneurship studies. Yet researchers have to come to agreement to the dimensionality of this important construct. EO is a multi-dimensional construct with varying impact on the performance and success of an enterprise in a developing context. Likewise, family ownership of the entrepreneurial business is one of the oldest phenomena in business circles. In developing countries family owned businesses makeup sizeable majority. The present study is conducted to investigate the role EO plays in the success of an enterprise with the moderating influence of family involvement. The study results indicate that proactiveness and autonomy are the most significant dimensions in the success of an enterprise. The results indicate that when family is taken as a moderator, the overall influence of EO dimensions is considerably reduced. The study concludes that cultural setting of entrepreneurial businesses and entrepreneurs themselves are subject to cultural norms and values and this cultural setting inhibit certain aspects of entrepreneurial activity, limiting the growth of entrepreneurship in a country. The study also recommends and points out future directions for further research.